Genetic mechanisms of the influence of light and phototransduction on Drosophila melanogaster lifespan - I. A. Solovev; M. V. Shaposhnikov; A. A. Moskalev (Вавиловский журнал генетики и селекции)
The light of the visible spectrum (with wavelengths of 380-780 nm) is one of the fundamental abiotic factors to which organisms have been adapting since the start of biological evolution on the Earth. Numerous literature sources establish a connection between the duration of exposure to daylight, carcinogenesis and longevity, convincingly showing a significant reduction in the incidence of cancer in blind people, as well as in animal models. On the other hand, the stimulating nature of the effect of continuous illumination on reproductive function was noted, in particular, the effects of increasing the fecundity of females of various species are known. Increase in motor activity and, as a result, in metabolic rate and thermogenesis during permanent exposure to light also reduces the body's energy reserves and lifespan. In principle, in the context of aging, not only the exposure time, but also the age at the onset of exposure to constant illumination matter, the reverse effects are valid for the maintenance of experimental animals in the constant darkness. Over the long period of the evolution of light signal transduction systems, many mechanisms have emerged that allow to form an adequate response of the organism to illumination, modulating the highly conservative signaling cascades, including those associated with aging and lifespan (FOXO, SIRT1, NF-kB, mTOR/S6k, PPARa, etc). In this review, we consider the relationship between lifespan, photoregimens, and also the expression of the genes encoding the phototransduction cascade and the circadian oscillator elements of animal cells. In the present paper, basic transducers of light and other signals, such as the family of TRP receptors, G proteins, phospholipase C, and others, are considered in the context of aging and longevity. A relationship between the mechanisms of thermoreception, the temperature synchronization of the circadian oscillator and the life span is established in the review. Analysis of experimental data obtained from the Drosophila melano-gaster model allowed us to formulate the hypothesis of age-dependent photoresistance - a gradual decrease in the expression of genes associated with phototransduction and circadian oscillators, leading to deterioration in the ability to adapt to the photoregimen and to the increase in the rate of aging.